Relações dialógicas no processo de ressignificação do discurso científico em enunciados de notícia de popularização da ciência - Edmundson, Maria Verônica Andrade da Silveira (2017)
The distinct aspects that involve the sphere of human activity, in which the Popularisation of Science News (PSN) is produced in the written mode, and the types of dialogic relations in the process of resignification of Scientific Discourse (SD) for the Discourse of Science Popularisation (DSP), present in the utterances of PSN, are indispensable elements to provide the wider public in society with access to scientific knowledge. We defend the thesis that the types of dialogic relations on which is grounded the process of resignification of the utterances of SD in utterances of the PSN genre – a heterodiscursive genre – favour the construction of the meaning of the utterances by the PSN reading public. The guiding question for this research is: What types of dialogic relations are relevant to describe the process of resignification of SD in the utterances of PSN? Inserting ourselves into the dialogic perspective of language, the proposal of this research is to analyse the boundaries of the process of resignification from one discourse to another, from one form of communicating to another. In this way, grounded on the Bakhtinian concepts of language, the research has the general aim of analysing and identifying the types of dialogic relations that are the basis of the process of resignification of SD to PSN. The research corpus consists of two representative samples of SD: a scientific article, published in the CELL journal, and a report, published in the Science magazine. As for samples of DSP, we chose three PSNs published on internet sites, as follows: two from the American website Sciencedaily, specialising in science news, and one from the Brazilian journalism portal G1. The choice of these PSNs, which popularised one of the most significant discoveries of the 2000-2010 decade, is justified by the relevance of the contents that they cover. As regards the methodology adopted, this is a qualitative piece of research of a descriptive-explicative nature, in which the data are analysed and interpreted starting from methodological parameters through means of which are analysed the thematic content, the compositional form and the style of the author-enunciator, that is, the journalist, that will reflect his/her axiological positioning and the social context of this genre. The epistemological framework adopted is the one guided by the work arising from the Enunciative Theory on the dialogical perspective of language based on the theoretical formulation of Bakhtin, and of the Circle, such as Bakhtin (1976, 2006, 2013, 2014), Bakhtin/Volochinov (1997, 1976) and Volochinov (1930). Besides this, we have taken as basis of study the analysis of scientific articles developed by Swales (1999 and 2005). With respect to concepts in the journalistic sphere, we have adopted as referential the theoretical assumptions of Bueno (1985, 2010, 2014), Lustosa (1996), Bahia (1990) and Lage (2008, 2011, 2012). The results indicate that the author-enunciator of the PSN acts as mediator between the scientists and society and that there are different types of dialogic relations in the process of resignification of the SD to utterances in the PSN, amongst which three main dimensions stand out: dialogic relations of proximity with the presumed recipient, between preceding and following utterances, and through the schemes of resignification of the discourse of the other.